The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsomega.2c04314
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrodeoxygenation of Lignin-Derived Phenols to Aromatics Catalyzed by Nb2O5-Supported Iridium

Abstract: The dominating catalytic approach to aromatic hydrocarbons from renewables, deoxygenation of phenol-rich depolymerized lignin bio-oils, is hard to achieve: hydrodeoxygenation (HDO) of phenols typically leads to the loss of aromaticity and to non-negligible fractions of cyclohexanones and cyclohexanols. Here, we report a catalyst, niobia-supported iridium nanoparticles (Ir@Nb 2 O 5 ), which combines full conversion in the HDO of lignin-derived phenols with appreciab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…267,268 From this point of view, both chemocatalytic and biological pathways have been developed for the defunctionalization of lignin monomers. 267,405,[418][419][420][421] Among the possible routes for chemocatalytic upgrading of phenolic monomers, their defunctionalization through HDO reactions is particularly attractive for decreasing the complexity of the mixture of monomeric products, as well as the oxygen content of the produced molecules. 267,405,422,423 Depending on the applied process conditions, HDO of phenolic monomers can yield alkanes, aromatic hydrocarbons, phenols, or cyclohexanols (Fig.…”
Section: Upgrading Lignin Monomers To Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…267,268 From this point of view, both chemocatalytic and biological pathways have been developed for the defunctionalization of lignin monomers. 267,405,[418][419][420][421] Among the possible routes for chemocatalytic upgrading of phenolic monomers, their defunctionalization through HDO reactions is particularly attractive for decreasing the complexity of the mixture of monomeric products, as well as the oxygen content of the produced molecules. 267,405,422,423 Depending on the applied process conditions, HDO of phenolic monomers can yield alkanes, aromatic hydrocarbons, phenols, or cyclohexanols (Fig.…”
Section: Upgrading Lignin Monomers To Chemicalsmentioning
confidence: 99%
“…267,268 From this point of view, both chemocatalytic and biological pathways have been developed for the defunctionalization of lignin monomers. 267,405,418–421…”
Section: Valorization Of the Isolated Lignin Fractionsmentioning
confidence: 99%
“…They found that the selectivity is governed by metal and acid sites, catalyst amount, hydrogen pressure, and temperature. Heterogeneous metal catalysts are commonly synthesized by co‐precipitation, wet‐impregnation, precipitation‐impregnation, sol‐gel, among other methods [22–24] . However, this process has significant drawback, due to the size and shape of metal particles is difficult to control and tend to form agglomerates of metal particles, leading to a loss of active phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Nb 2 O 5 can be used as an efficient catalytic deoxygenation support . However, its deoxygenation efficiency is also related to some key factors such as oxygen vacancy content, acidity, structural properties, interaction with active metals, etc.…”
Section: Introductionmentioning
confidence: 99%
“…26 Therefore, Nb 2 O 5 can be used as an efficient catalytic deoxygenation support. 27 However, its deoxygenation efficiency is also related to some key factors such as oxygen vacancy content, acidity, structural properties, interaction with active metals, etc. The crystal structure of Nb 2 O 5 has a great impact on the above properties; thus, it is necessary to conduct in-depth research on the catalytic effect of Nb 2 O 5 crystal structures.…”
Section: Introductionmentioning
confidence: 99%